Physical Development And Physicochemical Characterization Of A Soy-Based Cream Cheese - Lim, Ting Jin (2010)
Soy-based cream cheese (SCC) was developed with textural properties similar to those of commercial dairy cream cheese (DCC) via the addition of microbial transglutaminase (MTG), soy protein isolate (SPI) and maltodextrin (MD). Response surface methodology (RSM) was employed to determine the effects of MTG, MD and SPI on firmness of SCC. The second-order model was significant with only a 9.76% variation not explained by the model and this model successfully predicted and developed a SCC model with similar firmness as that of DCC. MTG and SPI were found to increase the firmness of SCC, whereas MD decreased the firmness of SCC. Texture profile analysis (TPA) showed that the textural properties of SCC were affected by the concentrations of MTG and SPI. Rheological measurements revealed that SCC was more solid-like at room temperature, but less elastic at refrigerated temperature compared to DCC. The micrographs obtained from the scanning electron microscope (SEM) affirmed the textural changes of SCC attributed to the cross-linking. The sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) profile of SCC illustrated the effect of the cross-linking of soy proteins by MTG. Physicochemical analyses also revealed that SCC possessed higher nutritional values due to its lower fat composition (less than 2% w/w), reduced saturated fatty acid, lower ratios of saturated fatty acids to unsaturated fatty acids (SFA/UFA) and low level of trans fat content (less than 0.01% w/w) compared to DCC.